Developing a Continuous Learning Model to Enhance Students' Knowledge in History Subjects - Abdurrahman Kader (Universitas Negeri Makassar, 2022)
The purpose of this writing is to find out the development of a continuous learning model in increasing student knowledge in History subjects. This writing is a descriptive analysis of thoughts related to historical learning models so that this writing can give birth to new thoughts related to the learning process that is delivered continuously / repeatedly with the same learning outcomes from class X, to class XII but with a cognitive approach, because the continuous learning model using different approaches at each grade level can increase students' knowledge in understanding the subject matter history lessons. The application of continuous learning can increase students' knowledge because teachers can use diverse approaches and techniques so that students can absorb knowledge well. The development of sustainable kind of classroom can improve understanding and student knowledge in studying material history because of learning which he delivered recurring then information it stays is in the labyrinth of the brain.